Perancangan Buku Mewarnai Interaktif Berbasis Teknologi Augmented Reality Dengan Unity Region Capture - Ronan Rizky Mayrendra; Bhanu Sri Nugraha (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
Coloring activities are one of the activities most liked by early childhood, by coloring they can express their abilities based on their unlimited imagination. On the other hand, rapid technological developments actually make young children prefer to play smartphones by watching videos or playing games that are not beneficial for growth and development. Based on the problems above, the authors developed an application prototype for smartphones where this application can be integrated with mammal coloring books. This application uses Augmented Reality technology so that later there are virtual objects that appear as if they were in the real world. Using design and production methods users can see colored objects in 3D and look as if they were real. This application was made for Android mobile devices, and is expected to be especially useful for increasing children's creativity in the field of coloring, on the other hand it also encourages children who are addicted to smartphones to use smartphones for more useful activities. The test results stated that the interactive coloring book design could run smoothly as planned.